Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records - Brailovsky, Harry (Zootaxa, 2019)
Two new genera, Nepiomistus, gen. nov., and Protenoroides, gen. nov., and one new species, Nepiomistus eximius, sp. nov., from Ecuador are described. Protenoroides is used to accomodate a species previously included in the binomen Protenor tropicalis Distant, 1881. New distributional records for Esperanza texana Barber, 1906 and Protenor australis, Hussey, 1925 are included. Photographs of the dorsal and lateral habitus, a close up of the head and thorax in lateral view, and the parameres of the genera included in the New World Micrelytrini are presented. An illustrated identification key for the 13 genera included in the New World Micrelytrini is added.